2015
DOI: 10.1186/s13075-015-0661-y
|View full text |Cite
|
Sign up to set email alerts
|

Laminin-rich blood vessels display activated growth factor signaling and act as the proliferation centers in Dupuytren’s contracture

Abstract: IntroductionDupuytren’s contracture (DC) is a chronic fibroproliferative disease of the hand, which is characterized by uncontrolled proliferation of atypical myofibroblasts at the cellular level. We hypothesized that specific areas of the DC tissue are sustaining the cell proliferation and studied the potential molecular determinants that might contribute to the formation of such niches.MethodsWe studied the expression pattern of cell proliferation marker Ki67, phosphorylated AKT (Ak mouse strain thymoma) kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 32 publications
(38 reference statements)
2
18
1
1
Order By: Relevance
“…4,16 However, what remains unknown is the origin of these cells. 1,2 DD manifests as a nodule through aberrant, uncontrolled proliferation of myofibroblasts 2,16 which progresses to form thick collagenous cords along lines of tension, resulting in fixed flexion contracture of the affected digits with functional loss. 1,2 …”
mentioning
confidence: 99%
“…4,16 However, what remains unknown is the origin of these cells. 1,2 DD manifests as a nodule through aberrant, uncontrolled proliferation of myofibroblasts 2,16 which progresses to form thick collagenous cords along lines of tension, resulting in fixed flexion contracture of the affected digits with functional loss. 1,2 …”
mentioning
confidence: 99%
“…Pericytes, the endothelium-covering cells, have been attributed with stem cell properties in several organs [59], which is likely to be the case also in DD fibrosis. Vessel structures that contain high levels of laminins, a key basal membrane component of the connective tissue, facilitate proliferation of myofibroblasts evident by proliferating centres in the vicinity of these vessels [60••]. Endothelial cell and mesenchymal stem cell (MSC)-enriched protein CD105 (type III receptor, endoglin) has been found to be expressed near these proliferation centres.…”
Section: Contribution Of Stem/progenitor Cells In Ddmentioning
confidence: 99%
“…According to recent reports, myofibroblasts play a leading role in the patomechanism of tendon contractures [12,18]. It is suggested that calcium plays a key role not only in the mechanism of myofibroblast contraction, but also in the process of inter-and extracellular signalling [13]. Among other signalling disorders, there is also a Wnt/beta-catenin signalling disruption [11].…”
Section: Introductionmentioning
confidence: 99%
“…At the end of the physiological process of wound healing, myofibroblasts disappear as a result of apoptosis, yet once the control of this process is impaired, the beneficial processes of remodelling might lead to organ deformity and loss of function [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation